Association of Anxiety and Depressive Symptoms with Thyroid Hormone Concentrations in Patients with Primary Bone Tumors - Ao, Man; Xu, Kun; Pan, Yujun; Wang, Shuping; Fu, Guoquan (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: Timely identification and intervention of psychological disorders bear significant import in ameliorating the ensuing therapeutic trajectories in primary bone tumor patients. Moreover, perturbations in thyroxine and thyroid-stimulating hormone (TSH) levels have been linked to manifestations of depressive and anxiety-related symptoms. However, the precise interplay governing the nexus of anxiety, depression, and the levels of thyroxine and TSH within the context of primary bone tumor patients remains presently unexplored. Objective: The objective of this study is to investigate the potential correlation between the hypothalamus- pituitary-thyroxine (HPT) axis and the depressive as well as anxious states observed in patients afflicted with bone tumors. Methods: Patients with primary bone tumors were required to accept the assessments of anxiety and depressive symptoms as well as thyroid axis hormone concentrations. The depressive and anxiety symptoms were assessed using the Hamilton Depression Rating Scale (HAMD) and the Hamilton Anxiety Scale (HAMA) score. During each follow-up, peripheral venous blood samples were collected for subsequent analysis using radioimmunoassay methods to measure serum- free T3, free T4, and TSH levels, with the calculated free T3 to free T4 ratio indicating peripheral free T4 to free T3 conversion. Tests for trend were conducted to assess thyroid axis hormone concentrations, HAMA scores, and HAMD scores, while the correlation between HAMA or HAMD scores and thyroid axis hormone concentrations was examined through univariate regression analyses. Results: The study included 30 primary bone tumor patients. Initial high HAMA and HAMD scores decreased over a year after surgery (P < 0.05), reflecting diminishing anxiety and depression. TSH levels reduced postoperatively, contrasting with increased free-T3 and free-T4 levels (p < 0.01). Multivariate analysis affirmed that positive correlations were noted between TSH and anxiety/depression scores, while free-T3 correlated negatively, adjusted for demographic factors (p < 0.05). No significant associations emerged between HAMA/HAMD scores and free-T4 or free-T3 to free-T4 ratio (p > 0.05). Conclusion: The early identification of the low T3 syndrome could prove instrumental in both intervening and preventing adverse emotional states associated with primary bone tumors.
Keywords: Primary bone tumors